Dry cow management program - John F. Smith (Kansas Agricultural Experiment Station Research Reports, 1987)
Dry cows do not require the intensive daily management of cows in early lactation, but the handling of mastitis treatments, feeding regimen, and grouping are of utmost importance in determining how the cows will perform in the subsequent lactation. The dry period is the time we allow for the cow to regenerate milk-secreting tissue, combat mastitis, and prepare for the next lactation. The body condition of each cow should be moderate before drying off. Each quarter should be treated with a commercial dry cow mastitis treatment, then the cow should be separated from the milking herd for observation and fed a diet specifically formulated for the dry period. The final stages of the dry period are used to prepare the cow for acute changes that occur at calving, including exposure to different feeds, and increasing grain intake 2 weeks before calving. Increased grain intake during the final 2 weeks allows the rumen to adjust so maximal intake of dry matter is achieved sooner after calving. This helps offset the negative energy balance that dairy cows experience during early lactation. Following these general guidelines during the dry period will decrease problems encountered at or near calving, Which, in turn, will allow the cow to reach her maximum genetic potential.; Dairy Day, 1987, Kansas State University, Manhattan, KS, 1987;
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-114-S; Report of progress (Kansas Agricultural Experiment Station); 527; Dairy; Dry cow; Management; Milk